Plug n=2 in the formula to get the second term.
Then plug a1= 6
So, second term = a2= -1/6
To get the third term plug n=3.
Then plug a2= -1/6
So, third term = a3= 6
Plug n=4 in the formula to get the fourth term.
Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*See Solution
Q: Please graph the given function and its inverse: f(x) .= √x-2 Thank you!
A: The given function is,
Q: Simplify 5/a^2-4a+3/3/a-3+4/a-1
Q: Assume that in one country in 2005, 12.5% of the population was 65 or older. By 2050, this percent...
Q: Factor completely: 9 x^2 y^4 + 6 x ^6 y^2 - 12 x^3 y^3
Q: A promissory note will pay $48,000 at maturity 13 years from now. If you pay $23,000 for the note no...
A: Given,A promissory note will pay $48,000 at maturity 13 years from now and the initial payment is $2...
Q: question 4
A: First we try to graph y=x^2-2x-2 and y=2x-x^2+2.We make table for both of them.
Q: (5y2+4y+2)(y2+3y+4)? Multiply?
A: Click to see the answer
Q: Solve the system of equations consisting of x2 + y2 = 49 and x2 + 64y2 = 64. (Order your answers fro...
A: Solving system of two equations.
Q: Find the sum 5 (5+2) i-0
A: The given expression is